HIV among men who have sex with men in the Caribbean: reaching the left behind - Willy Dunbar; Jean William Pape; Yves Coppieters (Pan American Health Organization, 2021)
Objectives. To present the epidemiology, social and cultural factors driving the HIV epidemic among men who have sex with men (MSM) in the Caribbean region and to highlight the regional and national responses, and what remains to be addressed to close the gaps in order to ending AIDS by 2030. Methods. A literature review was performed in the following databases: PubMed and Scopus. Articles published in the past 10 years were selected. The outcomes of interest were sociocultural risk factors, description of regional and national efforts and potential challenges and barriers to effective control of the epidemic among MSM. This report concentrates exclusively on publications related to MSM living in the Caribbean countries. Results. 11 peer-reviewed studies, 9 grey literature reports and programme frameworks were thematically analysed. The prevalence of HIV among MSM is high and the rates also do vary among Caribbean countries. Several factors influence the epidemic among MSM in the Caribbean but stigma and discrimination underlie the social vulnerability and play a central role in driving the HIV epidemic. Conclusions. To end the AIDS epidemic by 2030, MSM can no longer be kept unchecked in the era of the Sustainable Development Goals with the motto 'Leave no one behind'.